Impact of restructuring policies on organizational learnings in China. - Sun, Shuwen. (2008)
The purpose of this research is to examine the impact of the differences between economic transitions in China and Central and Eastern Europe on organizational learning. Our research aims to advance the theorization initiated by Newman (2000). She argues that rapid change inhibits second-order learning in Central and Eastern European countries. Our research has found out that the reform process of Chinese companies can be perceived to be the antithesis of the reform of Central and Eastern Europe. The government played a more important role in guiding the reform, and the gradual process helped organizational learning. As a result, these factors facilitated organizational transformation.